Reinventing medieval liturgy in Victorian England Thomas Frederick Simmons and the Lay Folks' Mass Book - Jasper, David 1951-; Smith, J. J. 1955- (The Boydell Press, 2023)
In 1879, Canon Thomas Frederick Simmons edited the late medieval poem now known as 'The Lay Folks' Mass Book' creating what remains the standard edition of the text. This volume shows how Simmons' interest in the text was related profoundly to contemporary debates about worship in the Church of England, and how he used his medievalist researches as the basis for the most important attempt at Prayer Book revision between the Reformation and the twentieth century
Erscheinungsdatum der Online-Ausgabe: March 2024
Title from publisher's bibliographic system (viewed on 08 Mar 2024)
Keywords: Thoresby, John -- -1373 -- Lay folks' catechism; Simmons, Thomas Frederick -- 1815-1884; Early English Text Society; Medievalism -- Great Britain -- History -- 19th century; Catechisms, English -- Early works to 1800